2018
DOI: 10.1021/acsbiomaterials.8b00228
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Augmented Nanofiber Scaffolds Trigger Gene Expression Switching of Four Cancer Cell Types

Abstract: Three-dimensional (3D) customized scaffolds are anticipated to provide new frontiers in cell manipulation and advanced therapy methods. Here, we demonstrate the application of hybrid 3D porous scaffolds, representing networks of highly aligned self-assembled ceramic nanofibers, for culturing four types of cancer cells. Ultrahigh aspect ratio (∼107) of graphene augmented fibers of tailored nanotopology is shown as an alternative tool to substantially affect cancerous gene expression, eventually due to differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
(153 reference statements)
0
12
0
Order By: Relevance
“…On the one hand, the biomimetic nano-micron morphology contributes to the good cell functions. Although there is no report on cancer cells cultured in nano-microfibrous scaffolds, a few previous studies confirmed the suitability of nanofibrous scaffolds for cancer cell growth and survival (Sims-Mourtada et al 2014;Kazantseva et al 2018;Bae et al 2011), which indicates that both normal and cancerous tissues are responsive to ECMlike microenvironments. Here, we combine nanofibers with microfibers to provide a more elaborate ECMlike microenvironment than single nanofibers or microfibers.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the biomimetic nano-micron morphology contributes to the good cell functions. Although there is no report on cancer cells cultured in nano-microfibrous scaffolds, a few previous studies confirmed the suitability of nanofibrous scaffolds for cancer cell growth and survival (Sims-Mourtada et al 2014;Kazantseva et al 2018;Bae et al 2011), which indicates that both normal and cancerous tissues are responsive to ECMlike microenvironments. Here, we combine nanofibers with microfibers to provide a more elaborate ECMlike microenvironment than single nanofibers or microfibers.…”
Section: Discussionmentioning
confidence: 99%
“…Growth on highly aligned graphene fibers changed the morphology from flat to a more rounded shape as the cells enveloped the fibers. In addition, increased gene expression of promigratory and pro-invasion markers were observed [172]. This represents a potential system to examine the more migratory or more metastatic NB cells, and develop therapeutics aimed at effectively inhibiting those cells.…”
Section: Hydrogels and Scaffolds For 3d Tumor Growthmentioning
confidence: 98%
“…Scaffold based studies have also been used for biomechanical modeling. One scaffold-based study used graphene-augmented nanofiber scaffolds to determine the impact of an "out-of-comfort" nanobiomechanical environment for NB cells [172]. Growth on highly aligned graphene fibers changed the morphology from flat to a more rounded shape as the cells enveloped the fibers.…”
Section: Hydrogels and Scaffolds For 3d Tumor Growthmentioning
confidence: 99%
“…Micro-and nano-fibers created by electrospinning guarantee high porosity of the structures and favor neuroblastoma cell proliferation and adhesion, while promoting neurite out-growth (60). The usefulness of the highly aligned graphene-augmented inorganic nanofiber (GAIN) scaffolds for biomedical cancer research has also been proven for several tumor cell types including neuroblastoma (61). Although they do not allow tumor-like 3D cell organization entirely, these scaffolds open an opportunity for a fast and highly reproducible validation of anti-cancer drugs oriented toward the modulation of cell migration.…”
Section: Cast In Vitro 3d Models For Studying Neuroblastomamentioning
confidence: 99%